Influence of amount and aspect ratio on direct shear behavior of fiber reinforced concrete - Roughani, Hooman (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2013)
ABSTRACT: It is generally believed that one of the most important steps in the design of concrete members is the shear design. The main objective of this study is to analyze the shear behavior of two different types of fiber reinforced concrete. This experiment of reinforcement has been carried out with different amounts of steel fibers and aspect ratios. The current study therefore will conduct an experiment on a comparison between steel fibers reinforced concrete and plain concrete. The materials used in the concrete mix are blast furnace slag cement (BFSC), crushed limestone coarse and fine aggregates from Beparmak Mountains. Other materials include hooked-end steel fibers, super-plasticizing admixture, and drinkable water. Water to cement ratio for normal strength concrete is 0.50 and for high strength is 0.43. In the shear test the strength of reinforced concrete went up by increasing the volume fraction of fiber. Increasing volume from 0 to 1.5% increased 122.7% shear strength for C30, l/d 65. Similar results were obtained for C30, with l/d 80. Volume fractions of steel fibers ranging from 0 to 0.5 %, shear strength increased 35 % and from 0 to 1%, 78.7% increase in shear strength were obtained. In high strength concrete C50 the shear strength was affected by adding volume fraction of fibers. The results show that applied shear strength increased 151.4% for 1.5% amount of steel fiber and also 66% for 0.5% amount and 114% increased for 1% volume fraction of steel fibers. Results have shown that aspect ratio has no clear effect on shear strength. Because there is not much different between results of concrete with l/d 65 and concrete with l/d 80. Keywords: Shear strength, Steel fiber, Concrete class, Fiber reinforced concrete. ………………………………………………………………………………………………………………………… ÖZ: Genellikle betonarme eşemanların tasarımında göz önünde bulundurulan en önemli parametrelerden birisi kesme kuvvetleridir. Bu çalışmanın esas amacı ise iki farklı narinlik oranı ve miktarı olan çelik elyaf ile üretilen beton elamanların kesme kuvvetlerinin davranışlarının analiz edilmesidir. Kesme kuvvetlerinin ölçülmesi için kullanılan deney metodu ile elde edilen sonuçlar üretilen çelik elyaflı betonlar şahit beton ile kıyaslanmıştır. Betonların üretilmesi amacı ile kullanılan malzemeler ise curuflu çimento, beşparmak dağlarından elde edilen kırma kireçtaşı agragaları, çengelli çelik elyaf, kimyasal katkı ve içme suyudur. Su çimento oranı ise normal mukavemetli betonlarda 0,50, yüksek mukavemetli betonlarda ise 0,43 olarak tasarlanmıştır. Elde edilen sonuçlara bakıldığında ise betonda kullanılan çelik elyaf miktarının arttıkça kesme kuvvetine olumlu etki ederek artmasına neden olmuştur. Çelik lif miktarı sıfırdan %1,5‘e yükseltildiği zaman kesme kuvveti C30 l/d 65 (beton sınıfı C30, çelik elyaf narinlik oranı 65) betonunda %122,7 artışa sebep olmuştur. Benzer sonuçlar C30 l/d 80 (beton sınıfı C30, çelik elyaf narinlik oranı 80) betonu için de elde edilmiştir. Çelik elyaf miktarı %0,5 olan betonlarda kesme kuvveti artış oranı %35, çelik elyaf miktarı %1 olan betonlarda ise kesme kuvveti artış oranı %78,7 olmuştur. Beton sınıfı C50 olan çelik elyaflı betonlarda ise %1,5 elyaf miktarı kesme kuvvetini %151,4, %0,5 olan çelik elyaf miktarı ise kesme kuvvetini %66 artırmıştır.Yüzde 1 vi olan çelik elyaf miktarı ise kesme kuvvetini %114 oranında artırmıştır. Bunların yanında elde edilen sonuçlara bakıldığında çelik elyaf narinlik oranının kesme kuvveti üzerine herhangi belirgin bir etkisi olmadığı görülmüştür. AnahtarKelimeler: Kesmedirenci, çelikelyaf, betonsınıfı, çelikelyaflıbeton.
Master of Science in Civil Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2013. Supervisor: Prof. Dr. Özgür Eren.
Keywords: Civil Engineering; Reinforced concrete, Fiber.